Robust stability of positive continuous-time linear systems with delays - Busłowicz, Mikołaj (Zielona Góra: Uniwersytet Zielonogórski)
The paper is devoted to the problem of robust stability of positive continuous-time linear systems with delays with structured perturbations of state matrices. Simple necessary and sufficient conditions for robust stability in the general case and in the case of systems with a linear uncertainty structure in two sub-cases: (i) a unity rank uncertainty structure and (ii) nonnegative perturbation matrices are established. The problems are illustrated with numerical examples.
Keywords: positive continuous-time linear system; delays; robust stability; linear uncertainty; interval system